Evaluation of Ocular Versions in Graves’ Orbitopathy: Correlation between the Qualitative Clinical Method and the Quantitative Photographic Method - Cristiane de Almeida Leite; Thaís de Sousa Pereira; Jeane Chiang; Allan C. Pieroni Gonçalves; Mário L. R. Monteiro (Journal of Ophthalmology)
Purpose. To assess the agreement between the qualitative clinical method and the quantitative photographic method of evaluating normal and abnormal ocular versions in patients with inactive Graves’ orbitopathy (GO). Methods. Forty-two patients with inactive GO had their ocular versions evaluated clinically according to three categories: normal, moderate alterations (−1 or −2 hypofunction), and severe alterations (−3 or −4 hypofunction). The subjects were photographed in the 9 positions of gaze, and the extent (mm) of eye movement in each position was estimated using Photoshop® and ImageJ and converted into degrees with a well-established method. The agreement between the two methods (qualitative vs. quantitative) for classifying ocular versions as normal or abnormal was assessed. Results. The mean quantitative measurements of versions were significantly different for each clinical category (normal, moderate alterations, and severe alterations) in the following five positions: abduction, adduction, elevation in abduction, elevation, and elevation in adduction (p<0.001). No such pattern was observed for the three infraversion positions (depression in abduction, p=0.573; depression, p=0.468; depression in adduction, p=0.268). Conclusion. The agreement was strong between the quantitative photographic method and the qualitative clinical method of classifying ocular versions, especially in lateral and supraversions, which are typically affected in GO. Digital photography is recommended for the assessment of ocular versions due to its practicality, suitability for telemedicine applications, and ease of monitoring during follow-up. This trial is registered with NCT03278964.